Investigate the Process Parameter on the Friction Stir Welding of Dissimilar Aluminium Alloys - R. Raja; A. Parthiban; S. Nandha Gopan; Derese Degefa (Advances in Materials Science and Engineering)
The welding of different materials with an acceptable quality range is an emerging study area; engineers and scientists worldwide have long been concerned with dissimilar welding materials. This study focuses on determining the friction stir welding of different aluminuim alloys; an experimental investigation was conducted (AA7475-T651 and AA2219-O). It also describes the FSW process parameters and response measurement for defining weld quality and the procedure for measuring them. Taguchi L27, orthogonal array method, is preferred for optimizing FSW parameters such as shoulder diameter, tool rotational speed, and traverse speed. The effect of welding parameters is investigated through the ANOVA table and graphs. The SEM analysis investigates the fracture and micrographic analysis in the heat-affected zone and thermo-mechanically affected zone.